A proposed methodology in providing the content and procedures of social studies textbooks - Velasco, Violeta D.
This study presents a methodology that provides content and procedure in the new social studies textbooks, thus serving as a springboard for writing textbooks that will meet the requirements of the social studies curriculum reform.
Thesis (M.A.T. Social Studies)--University of the Philippines
Keywords: Social sciences -- Textbooks